2006
DOI: 10.1038/sj.leu.2404385
|View full text |Cite
|
Sign up to set email alerts
|

Megakaryocytic dysfunction in myelodysplastic syndromes and idiopathic thrombocytopenic purpura is in part due to different forms of cell death

Abstract: Platelet production requires compartmentalized caspase activation within megakaryocytes. This eventually results in platelet release in conjunction with apoptosis of the remaining megakaryocyte. Recent studies have indicated that in low-risk myelodysplastic syndromes (MDS) and idiopathic thrombocytopenic purpura (ITP), premature cell death of megakaryocytes may contribute to thrombocytopenia. Different cell death patterns have been identified in megakaryocytes in these disorders. Growing evidence suggests that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 47 publications
(66 reference statements)
1
38
0
Order By: Relevance
“…on May 10, 2018. by guest www.bloodjournal.org From including necrosis, apoptosis, and para-apoptosis have been used to describe the various processes observed. 36 In comparing our observations with those published, it is interesting to note that megakaryocytes in ITP patients 33 share features similar to those of dying Mcl-1 Pf4⌬/Pf4⌬ cells. Thus, in addition to the established role of Bak/Bax-mediated apoptosis in mediating chemotherapy-induced thrombocytopenia, 9 it is possible activation of the intrinsic pathway plays a role in other disorders associated with impaired platelet production.…”
Section: Discussionsupporting
confidence: 63%
“…on May 10, 2018. by guest www.bloodjournal.org From including necrosis, apoptosis, and para-apoptosis have been used to describe the various processes observed. 36 In comparing our observations with those published, it is interesting to note that megakaryocytes in ITP patients 33 share features similar to those of dying Mcl-1 Pf4⌬/Pf4⌬ cells. Thus, in addition to the established role of Bak/Bax-mediated apoptosis in mediating chemotherapy-induced thrombocytopenia, 9 it is possible activation of the intrinsic pathway plays a role in other disorders associated with impaired platelet production.…”
Section: Discussionsupporting
confidence: 63%
“…Apoptosis of dysplastic megakaryocytes and shortened platelet life expectancy in the BM, 51,52 together with a decreased platelet release by the dysplastic megakaryocytic precursors 53 reported in MDS, might contribute to explain the absence of an altered platelet immunophenotype in these cases, because under these conditions a normal immunophenotypic score may result from the immunophenotypic analysis of residual normal, rather than dysplastic, PB platelets.…”
Section: Discussionmentioning
confidence: 98%
“…30 Houwerzijl et al also reported that morphology compatible with para-apoptosis could be induced in cultured megakaryocytes with ITP plasma. 31 Whether para-apoptosis mediated megakaryocyte destruction was induced by autoantibody requires further investigation. Moreover, as with 2 important cyclins in megakaryocyte development and high ploidy formation, 32 the absence of cyclin D3 during the whole culture and low expression of cyclin B1 at early stage may have been the mechanism by which patient IgG inhibited megakaryocyte polyploidization.…”
Section: Discussionmentioning
confidence: 99%
“…Local caspase activation can lead to proplatelet formation and thus platelet release. 16,18,35 Houwerzijl et al 31 have reported that the inhibited megakaryocyte apoptosis may contribute to thrombocytopenia and augment dysfunctional megakaryocytes. We found reduced megakaryocyte apoptosis in the boosted megakaryocyte group, indicating that the reduced megakaryocyte apoptosis could be associated with a boosted megakaryocyte mass, but an impaired megakaryocyte maturation and reduced platelet production.…”
Section: Discussionmentioning
confidence: 99%